Strategi Pemerintah Desa Ranggagata Guna Meningkatkan Perekonomian Masyarakat - Sripe Wafiq Azizah; Ilham Zitri; Hidayatullah Hidayatullah; Azwar Subandi (Universitas Muhammadiyah Mataram, 2026)
Rural economic development is an important aspect of improving the welfare of rural communities. However, in many regions, including West Nusa Tenggara Province (NTB), rural economic growth still faces various limitations. Ranggagata Village in Central Lombok Regency is an agricultural village where the majority of the population depends on seasonal rice farming for their livelihood. This condition causes unstable community income and encourages the emergence of various alternative economic strategies. This study aims to analyze the economic conditions of the Ranggagata Village community and the role of the village government in community economic empowerment efforts. The research method used is a qualitative approach with data collection techniques through field observations, interviews with village officials, BUMDes managers, and the community, as well as a documentation study of the APBDes and village planning documents. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, accompanied by data triangulation to maintain the validity of the findings. The results of the study show that the village economy is still dependent on a single agricultural sector, while BUMDes is not yet functioning optimally. The allocation of the economic empowerment budget in the APBDes is relatively low and is not fully in line with applicable regulations. This condition has given rise to the phenomenon of kioskization as a survival strategy for the community, but has not been able to improve welfare in a sustainable manner. This study recommends strengthening village economic institutions, increasing the allocation of empowerment budgets, and developing data-based local economic potential so that village economic development is more effective and sustainable